Standard of proof in judgement of the administrative improbity actions (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The purpose of this article is to examine the question of standards of proof in the judgement of administrative improbity actions. Among the standards of proof generally conceived and accepted, brought from US law, that is, the standard of preponderance of evidence, the standard of clear and convincing evidence and the standard of proof beyond reasonable doubt, the work aims to investigate which one should be adopted, or which ones should be adopted, in improbity proceedings, especially after the advent of Law 14. 230/2021, which, by making intense changes to the Administrative Improbity Law (Law 8.429/92), has placed the act of improbity, its characterization and its consequences in the area of sanctioning law. The method used to approach the subject was the hypothetical-deductive method and the methodology was a review of the literature and case law, especially from the Federal Supreme Court. Thus, after examining the doctrine and case law on the subject, it was concluded in this study that, in order to apply the sanctions provided for in the Improbity Law, the standard of proof required must be clear and convincing evidence, while the less demanding standard of proof of preponderance of evidence applies to the judgment of the claim for reimbursement of the exchequer.Keywords: Standards of proof. Administrative impropriety action. Sanctions for impropriety. Clear and convincing evidence. Reimbursement to the exchequer. Preponderance of evidence.